Análise Comparativa entre Sistemas Construtivos de Laje Nervurada em Concreto Armado moldado no local em Edifícios Comerciais - Beseggio, Breno Oscar Chaves (Universidade Federal de São Carlos, 2020)
Slabs are fundamental in the structure of a building, in addition to being responsible for a large part of the consumption of materials and consequently of the cost of an enterprise. The emergence of new construction systems for ribbed slab became necessary to study them to enable an improvement of civil construction projects. This work aimed to be a comparative theoretical study between reinforced concrete slab construction systems molded on site in order to find the most suitable system for a commercial building. Among the construction systems of ribbed slab studied are the traditional ribbed slab, bubbledeck slab and holedeck slab, using solid slab as a reference. First, the specificities of each construction system were identified, paying attention to the construction methodology and the elements necessary for its execution. Then, slab cases with different spans, from 5.0 meters to 10.0 meters, were defined and dimensioned for the studied construction systems. The calculations were performed in an Excel® table according to ABNT NBR 6118: Design of concrete structures - procedure. The consumption of materials, own weight and height of the slab for each case studied was analyzed and it was concluded that the traditional ribbed slab proved to be the most suitable construction system for commercial buildings, as it reduced the average consumption of concrete by 48% and steel consumption by 8% in relation to solid slab, the average consumption of formwork increased only by 84%, in addition to decreasing in average self-weight by 48%, also in relation to solid slab, the height of the slab was shown be constantly smaller when compared to the bubbledeck and holedeck construction systems.
Comparative Analysis between Constructive Systems for Ribbed Slabs in cast-in-place concrete in Commercial Buildings
Keywords: laje nervurada; Concreto armado; Bubbledeck; Holedeck; Ribbed slab; Reinforced concrete; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS